An An Analysis Of The Incidence Of Sensorinural Hearing Loss Based On Type 2 Diabetes Mellitus And Obesity Factor: An Analysis Of The Incidence Of Sensorinural Hearing Loss Based On Type 2 Diabetes Mellitus And Obesity Factor - Dilla, Natasya Salsa; Wirayudha, Yan; Kurniati, Yuni Prastyo; Soekiswati, Siti (Faculty of Medicine, Universitas Jember, 2025)
Indonesia ranks fourth in Southeast Asia with a 2.3% prevalence of sensorineural hearing loss, a condition that may result from various risk factors including diabetes mellitus (DM) and obesity. DM can impair cochlear vascularization, while obesity significantly affects vascular function, potentially impacting the auditory system. This study aims to analyze the relationship between type 2 DM and obesity with sensorineural hearing loss. An observational analytic study with a cross-sectional approach was conducted on 64 participants aged 18–60 years, selected via purposive sampling. Type 2 DM was diagnosed by internal medicine consultants, and obesity was assessed using waist-to-hip ratio measurements. Data analysis employed Fisher's exact test and logistic regression. The study was ethically approved by the Health Ethics Committee of RS PKU Muhammadiyah Surakarta (No. 05/KEPK/RS.PKU/X/2024). Results showed a significant correlation between type 2 DM and sensorineural hearing loss (p=0.037) and between obesity and sensorineural hearing loss (p=0.001). The odds ratio for type 2 DM was 12.031, while for obesity it was 58.059, indicating that obesity poses a substantially higher risk. In conclusion, type 2 DM and obesity are significantly associated with the occurrence of sensorineural hearing loss, suggesting that addressing these risk factors may help reduce its prevalence. Keywords: Diabetes Melitus Tipe 2, Obesitas, Gangguan Pendengaran Sensorineural, Faktor Risiko.